2008
DOI: 10.1007/s11046-008-9097-0
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Oral Candida albicans by Chicken Egg Yolk Antibody (IgY)

Abstract: This study was conducted to measure Candida albicans-specific chicken egg yolk antibody (IgY) inhibition of fluconazole-sensitive and resistant strains of C. albicans in order to assess potential use in the prevention and treatment of oral candidiasis. In this study, laying hens were immunized, and IgY was extracted by water dilution. The Minimal Inhibitory Concentrations (MICs) of IgY for inhibiting C. albicans growth were determined using the broth microdilution method from the CLSI M27-A2 protocol. Fluconaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The therapeutic potential of polyclonal avian-derived IgY has been previously established for the treatment of Pseudomonas aeruginosa , which is in an ongoing phase III clinical trial under the auspices of the European Medicines Agencies [5860], in addition to treatment of Candida albicans , [61, 62], and many toxins and venoms [6365]. Although the animal models used in our study and others demonstrate the therapeutic efficacy of IgY, we recognize that there are potential obstacles that may arise in translating IgY therapeutics for human clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of polyclonal avian-derived IgY has been previously established for the treatment of Pseudomonas aeruginosa , which is in an ongoing phase III clinical trial under the auspices of the European Medicines Agencies [5860], in addition to treatment of Candida albicans , [61, 62], and many toxins and venoms [6365]. Although the animal models used in our study and others demonstrate the therapeutic efficacy of IgY, we recognize that there are potential obstacles that may arise in translating IgY therapeutics for human clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…If an effective preventive measure using IgYs against Candida is established, it will be possible to reduce the dosage of concomitant antifungal drugs and thus to reduce the emergence of resistant strains. Regarding this, Wang et al . reported that anti‐C.a.IgY inhibited the growth of C. albicans in vitro, and there was no correlation between drug resistance to fluconazole and the growth inhibition by IgY.…”
Section: Discussionmentioning
confidence: 97%
“…There were also other studies about antifungal IgYs such as anti-C. albicans IgYs [14,26,27]. One of the studies evaluated in vitro and in vivo effectiveness of IgY against C. albicans by using proteins from sonicated cells of C. albicans as antigen to immunized hens.…”
Section: Discussionmentioning
confidence: 99%
“…Effective protection against Salmonella enteritidis, Salmonella e. Typhimurium, Campylobacter jejuni, Escherichia coli ETEC, murine and bovine rotavirus, and bovine coronavirus infections in mice, pig, and calves has been obtained with the use of passively-administered egg yolk-derived antibodies [12]. Ample data have demonstrated the protection of IgY against different kinds of bacteria, virus, and parasites There are also reports about anti-fungi IgYs [13,14], reminding us that it may also be effective against T. rubrum.…”
Section: Introductionmentioning
confidence: 99%